2006
DOI: 10.1002/anie.200600048
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Chiral Ionic Liquids as Highly Efficient Asymmetric Organocatalysts for Michael Addition to Nitroolefins

Abstract: Catalytic combination: By combining the advantages of organocatalysts and ionic liquids, a functionalized chiral ionic liquid such as 1 can act as a highly efficient and reusable organocatalyst for the asymmetric Michael addition reaction of ketones and aldehydes with nitroalkenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
123
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 443 publications
(127 citation statements)
references
References 81 publications
2
123
0
2
Order By: Relevance
“…7 Luo and co-workers reported the preparation of chiral imidazolium salts derived from proline. 8 Inspired by their work, we prepared two types of chiral pyrrolidine-substituted imidazolium ¡-cetylpolyoxyethylene(10) ether sulfate, and found that (R)-3-butyl-2-methyl-1-(pyrrolidin-2-ylmethyl)-1H-imidazol-3-ium ¡-cetylpolyoxyethylene(10) ether sulfate (D-ProMe) derived from D-proline worked as an excellent activating agent for lipase PS (Figure 1). 9 An extraordinary acceleration was accomplished with perfect enantioselectivity for the D-ProMe-PS-catalyzed reaction, and a reaction 58 times faster (vs. lipase PS) was recorded.…”
mentioning
confidence: 99%
“…7 Luo and co-workers reported the preparation of chiral imidazolium salts derived from proline. 8 Inspired by their work, we prepared two types of chiral pyrrolidine-substituted imidazolium ¡-cetylpolyoxyethylene(10) ether sulfate, and found that (R)-3-butyl-2-methyl-1-(pyrrolidin-2-ylmethyl)-1H-imidazol-3-ium ¡-cetylpolyoxyethylene(10) ether sulfate (D-ProMe) derived from D-proline worked as an excellent activating agent for lipase PS (Figure 1). 9 An extraordinary acceleration was accomplished with perfect enantioselectivity for the D-ProMe-PS-catalyzed reaction, and a reaction 58 times faster (vs. lipase PS) was recorded.…”
mentioning
confidence: 99%
“…Ionic liquids (IL) have shown interesting ability as phase tags for organocatalysts. [6][7][8][9][10][11][12][13][14][15] Ionic liquid tagged catalysts can be tuned to attain a required physical property, such as solubility, or compatibility with the reaction medium and thermal stability. 16 In this way improved recovery and recycling and sometimes even better catalytic activity can be attained.…”
Section: Introductionmentioning
confidence: 99%
“…The FILs have shown great promise not only as alternative green solvents, but also as reagents or catalysts in organic transformations. [23][24][25][26] We have been interested in the use of functionalized ionic liquid-supported Schiff base, since Schiff base palladium(II) compounds are excellent candidates as N, O-bidentate ligands in catalysis owing to their desirable coordinating ability with palladium. In this paper, we wish to report the use of ionic liquid-supported Schiff base as the palladium (II) ligand to demonstrate their suitability in palladium-catalyzed Suzuki-Miyaura cross-coupling reactions.…”
Section: Introductionmentioning
confidence: 99%